The Effect Of Changing Curriculum On Students - Muliana Setia Hapsari; Hesty Widiastuty (Pusat Riset dan Inovasi Nasional, 2023)
One of the goals of education is to educate the life of the nation as stated in article 3 of Law no. 20 of 2003. For the realization of educational goals, it is necessary to have auxiliary media in implementing learning, namely the curriculum. Curriculum is a plan that is deliberately arranged to expedite the process of teaching and learning activities that are under the auspices, guidance and responsibilities of a school or educational institution to achieve educational goals. Therefore, there must be adjustments to the curriculum that is applied. The curriculum must be adapted to the needs of students and the achievements that must be met. This causes changes and developments in the curriculum on a regular basis. With regular curriculum changes, the question arises as to whether these changes in curriculum development have had an effect on students. Therefore, this research was conducted to determine the effect of curriculum changes on students. The research method used was literature study and a qualitative approach where researchers did not carry out direct analysis in the field, but only collected scientific papers from several sources related to the effect of curriculum changes on students. From the results of the study, the authors found that curriculum changes had a positive effect on learning outcomes, quality of education, increased competency and student learning but also had negative impacts such as the emergence of new problems for students such as student achievement decreased because they could not follow the new learning procedures. Curriculum development needs to be done for evaluation but must still be based on educational goals and the needs of students.